2020
DOI: 10.1093/eurheartj/ehaa649
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) lowering by alirocumab reduces the total burden of cardiovascular events independent of low-density lipoprotein cholesterol lowering: ODYSSEY OUTCOMES trial

Abstract: Aims Lipoprotein(a) concentration is associated with first cardiovascular events in clinical trials. It is unknown if this relationship holds for total (first and subsequent) events. In the ODYSSEY OUTCOMES trial in patients with recent acute coronary syndrome (ACS), the proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab reduced lipoprotein(a), low-density lipoprotein cholesterol (LDL-C), and cardiovascular events compared with placebo. This post hoc analysis determined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 17 publications
4
91
0
1
Order By: Relevance
“…This is generally in agreement with a population study showing that a reduction of Lp(a) concentration by 50 mg/dl lowered ASCVD risk by 20% in a secondary prevention setting 43 . The effect of Lp(a) on the risk of ASCVD events appears to be proportional to the absolute reduction in Lp(a), not the percent reduction 28 . The mean reduction in Lp(a) of 0.29 g/L with a PCSK9mAb could be approximately translated into 12%–15% reduction of ASCVD 28,43 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is generally in agreement with a population study showing that a reduction of Lp(a) concentration by 50 mg/dl lowered ASCVD risk by 20% in a secondary prevention setting 43 . The effect of Lp(a) on the risk of ASCVD events appears to be proportional to the absolute reduction in Lp(a), not the percent reduction 28 . The mean reduction in Lp(a) of 0.29 g/L with a PCSK9mAb could be approximately translated into 12%–15% reduction of ASCVD 28,43 .…”
Section: Discussionsupporting
confidence: 90%
“…Several large clinical trials of PCSK9mAb treatment have consistently demonstrated a significant reduction in Lp(a) concentration. [15][16][17][18] In the ODYSSEY OUTCOMES trial, 18,28 alirocumab reduced Lp(a) by −0.20 g/L (−22%) in a subset of patients with elevated Lp(a). In an observational study of four high-risk patients with elevated Lp(a), 6 month PCSK9mAb treatment lowered plasma Lp(a) levels by 12%.…”
Section: Lp(a) Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ODYSSEY OUTCOMES trial, it was shown that the Lp(a) reduction caused by alirocumab was related to the reduction of cardiovascular event risk and was not directly related to the simultaneous reduction of LDL. 75 In addition, after the use of alirocumab, for every 5 mg/L reduction of Lp(a), the total number of cardiovascular events was relatively reduced by 2.5%. 76 Although PCSK9 inhibitors can reduce plasma Lp(a) levels, the mechanism of action and clinical correlation remains to be explored.…”
Section: Treatment Of Increased Lp(a)mentioning
confidence: 94%
“…Available lipid-lowering therapies have little value for Lp(a) reduction. Aside from statins that could raise Lp(a) blood concentrations [68,69], PCSK9 inhibitors reduce Lp(a) levels by 25-30% [70] and there is evidence that reduction of Lp(a) elicited by these drugs might contribute to an improved prognosis in coronary disease patients [71]. Finally, for patients with progressive ASCVD and high plasma Lp(a), a possible approach sometimes used is lipoprotein apheresis [72].…”
Section: Lp(a)-novelties In the Era Of Rna-based Therapiesmentioning
confidence: 99%